Pengaruh Sosiodemografi, Pengetahuan, dan Perilaku Masyarakat DKI Jakarta dalam Kesediaan Membayar (Willingness To Pay) Limbah Masker Sekali Pakai di Masa Pandemi Covid-19 - Qurratu'ain, Yona; Herdiansyah, Herdis; Mizuno, Kosuke; Yona Qurratu'ain (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2025)
The use of masks is recommended to reduce the risk of widespread spread of the Covid-19 virus, but because of its use in high quantities in a short time, it has an impact on the high waste of disposable masks. The problem of high waste of masks that is not accompanied by good management is it has the potential to pollute the environment and disposable masks are included in the type of hazardous medical waste so that they require special waste management. The purpose of this study is to analyze the relationship between the sociodemographic characteristics of the people of DKI Jakarta and the Willingness to Pay (WTP) for disposable mask waste management to determine the WTP price for disposable mask waste management. The survey was conducted in DKI Jakarta Province by distributing questionnaires and obtained a total sample of 356 respondents. Furthermore, the analysis method used, the first is logistic regression analysis to determine the variables of sociodemographic characteristics that affect individual WTP. The next analysis method is to calculate WTP using the Contingent Valuation Method (CVM) and the question model with the Double Bounded dichotomous method. Based on the results, it is known that the dependent variables that can increase the WTP value are income (Δ+ 23.6%, p ≤ 0.05), type of healing treatment (Δ+ 100%, p ≤ 0.1), and knowledge (Δ+ 125.9%, p ≤ 0.01), where a value of Rp 28,578 is ideal for the cost of managing disposable mask waste.